Women representation and financial performance: Empirical analysis of healthcare sector in Indonesia - Nindiasari, Avininda Dewi; Nugroho, Hendrato Setiabudi (Journal of Contemporary Accounting, 2025)
This study aims to analyze the influence of women's representation on the board of directors on the financial performance of companies in the Indonesian health sector. Based on agency theory and previous literature, this study focuses on companies listed on the Indonesia Stock Exchange in the healthcare supplies & distributions, healthcare providers, and pharmaceuticals sub-sectors during the 2018-2022 period. Using the multiple linear regression method using EViews 13, the research results show that the proportion of women on the board of directors and female president directors do not have a significant influence on the company's financial performance, as measured through the liquidity index. These findings indicate that although there is an increase in the number of women in leadership positions, their contribution to the financial performance of companies in the health sector is not yet optimal. This supports the results of previous study which shows that the relationship between the presence of women on the board of directors and company performance can vary depending on the regulatory context, economic stability, and organizational culture in developing countries such as Indonesia.